Fractional nonconformance assessment : this dissertation is submitted for the degree of Doctor of Philosophy in Statistics, Massey University, New Zealand - Zhou, Xin (Massey University, 2020)
Food quality and safety are important due to the very nature of the product and the potentially severe consequences of a fault in the manufacturing process. Statistical tools are widely used in food quality assurance. However, measurement error, which is inevitable in food manufacturing due to the variation and inaccuracy of the measurement system, affects the performance of statistical quality control activities. The concept 𝘧𝘳𝘢𝘤𝘵𝘪𝘰𝘯𝘢𝘭 𝘯𝘰𝘯𝘤𝘰𝘯𝘧𝘰𝘳𝘮𝘢𝘯𝘤𝘦 was recently proposed to assess the probability of nonconformance for error-prone individual measurements. This thesis presents five pieces of work for fractional nonconformance assessment mainly suitable for food quality assurance and other applications. The new statistical methods developed pertain to control charting, acceptance sampling, and conformity testing areas. The application of the proposed methods is illustrated with real data from a leading New Zealand dairy product manufacturer. Interactive web-based Shiny apps providing step-by-step guidance to implement fractional nonconformance analytic tools are developed for practitioners.
Keywords: Food industry and trade; Quality control; Quality control; Statistical methods; acceptance sampling; conformity testing; control chart; food manufacturing; fractional nonconformance; guardbanding; measurement error; short run; statistical quality control; 490503 Computational statistics